Atoque – música – família: significados da educação musical em um projeto social - Tolio, Márcio Luiz (2017)
This study is linked to the Education and Arts - LP4 research line of the Graduation Program in Education of the Federal University of Santa Maria. It aimed to understand how families understand the musical and human development built in the project Atoque Social Percussion Workshop. In addition, a great number of social projects of children and young people through musical practices were studied. The choice to enter the family universe was not only due to the fact that there are few studies on the topic, but also due to personal motivation regarding some questions raised from the author as a musical educator and manager of the Atoque Social Percussion Workshop in Santa Maria - RS. The study provides material to think about proposals in the musical education of social projects in music, in addition to data that can collaborate to education in socio-cultural approaches. As a reference on the concept of family and musical education, the studies of GOMEZ (2009), BOZZETTO (2012), in which dialogue with SETTON (2002; 2008; 2009) and SOUZA (2004) in a sociological perspective of musical education were used. For the discussion on social projects and music education, the literature review was constituted on names such as KATER (2004); JUNGES (2013); KLEBER (2006); ROZZINI (2012), SOUZA (2004, 2014). The qualitative research used narrative interviews in a focal group (BAUER and GASKELL, 2002). Other references were used in the treatment of the data, such as PENNA (2012), FEIJÓ and MACEDO (2012), FIGUEIREDO (2010), SOBREIRA (2008), LOUREIRO (2004) and LAHIRE (1997). A great number of aspects are highlighted in the focus groups, including the importance of family involvement and cultural growth. The criticism of parents and of children's primary school teachers is relevant considering that students and families seem to be more involved in social projects than in schools.